Practical teachers and new technologies: challenges and opportunities for the construction of an innovative education - Cruz, José Ewerton Feitosa (Cadernos de Educação Tecnologia e Sociedade, 2018)
In this paper we discuss the relation between the use of new technologies and pedagogical innovation, given the technological advances of recent years, which has led to question the role of education and teacher in today's scenario of society, and reflection on new forms of learning. The article is in a literature and field research conducted in a public school of Bahia in order to verify the difficulties and possibilities of changes in teaching practice with the use of new technologies, an innovative educational perspective. In the field research were used the questionnaire and interview as tools applied to teachers and director and in the bibliographic research the following authors were used Brito e Da Purificação (2008) e Moran (2006 e 2007). Through the instruments used, we can verify that although teachers have notions of the importance of innovation, of the use of new technologies and the institution has several technological resources, these resources are little used, however, this does not mean that there is some significant change in practice teacher. The observed data have allowed us to understand that there is a small change in course in education with the use of new technologies. But still do requires large investments in education, teacher training, acquisition and maintenance of equipment.